The concern on halal food status catered to muslim consumers / Nur Adiba Rashidan and Fairuz Khalili - Rashidan, Nur Adiba; Khalili, Fairuz (2017)
Muslims account for about approximately 240 million of Southeast Asia’s population, it shows that Muslims hold the majority in the region. Mostly they are found in Brunei, Indonesia, and Malaysia while significant minority live in Thailand, Philippine and Cambodia. Rapidly expanding Muslim population within major market has created rising demand on I si am-friendly and Halal-certified products. Every food that is consumed by Muslims must meet the religious requirements as it is compulsory for them to obey and practiced in their daily routine. Lack of knowledge about Halal aspect and other elements will give an impact on the selection of Muslim consumers to choose food that especially those manufactured by non-Muslims. Thus, this study aims to identify the other causes than Halal logo that probably affect the purchasing transaction to Muslims by fulfilling the Sharia-compliance. The information of the consumer acceptance, Halal awareness, Halal accreditation and food ingredients was collected, selected and gathered from previous studies by other researchers. In this process, there was a need for research to be evaluated that the information is reliable and accurate to be used for this paper.